Bribery : a compliance handbook by Raj Chaada, partner, Hodge Jones Allen; Christopher Sallon QS, Doughty Street Chambers; Sam Tate, solicitor and visiting tutor, Durham University; with contributions from Nichola Higgins, barrister, Doughty Street Chambers.: a compliance handbook by Raj Chaada, partner, Hodge Jones Allen; Christopher Sallon QS, Doughty Street Chambers; Sam Tate, solicitor and visiting tutor, Durham University; with contributions from Nichola Higgins, barrister, Doughty Street Chambers. (2015) - Chada, Raj; Sallon, Christopher; (Lawyer), Tate, Sam; Higgins, Nichola
No abstract available